Evaluation of fatty liver in breast cancer patients and its metastatic potential - Ahmad, Nor Hayati (2021)
Background: Non-alcoholic fatty liver disease (NAFLD) has a higher prevalence among breast cancer patients compared to the normal population and is one of the risk factors for extrahepatic carcinogenesis. It has also increased the risk of primary tumour progression, risk of distant metastasis, and tumour recurrent. However, to date, not many clinical studies were done to evaluate fatty liver and metastatic risk. Thus, further clinical study is needed. This study aims to evaluate the association of fatty liver with distant metastasis and metastatic site. Methods: A cross-sectional study was conducted in Hospital Universiti Sains Malaysia (HUSM), Kelantan, Malaysia on histopathological confirmed female breast carcinoma patients from January 2014 till December 2020. The evaluation of fatty liver done were made on a plain CT abdomen images with reference of contrasted images. Three regions of interest (ROI) were drawn on the liver and spleen and the Hounsfield unit (HU) was documented. Liver to splenic ratio (L/S ratio) was calculated by dividing the average liver HU to splenic ratio. L/S ratio of less than 1.0 was taken as fatty liver. Evaluation of distant metastasis was also done. The association of fatty liver with distant metastasis and metastatic site were evaluated. Results: Out of 624 screened subjects, a total of 332 subjects with histopathologically proven breast carcinoma patients that underwent CT scan stage including thorax, abdomen, and pelvis scans were included as participants in th is study. Mean age was 53 years (SD±10.93) ranging from 28 to 82 years old, 45.5% (n—151) had tumour size of > 5 cm, 51.8% (n=l 72) had metastasis at diagnosis. The most common metastasis site was the lung, followed by bone and liver. The prevalence of fatty liver in the study population was 27.2% (n=91). This current study showed association of fatty liver with distant metastasis. Association of fatty liver with lung metastasis were also demonstrated. However, there was no association between fatty liver and distant metastasis or with the site of metastasis in tumour size of <5cm. Conclusion: Prevalence of fatty liver in breast carcinoma patients in our study was 27.2%, which corresponds to most of other studies. Considering the existing studies investigating the relationship between fatty liver and breast cancer, our study results showed a similar finding of an association of fatty liver with distant metastasis. Association of fatty liver with distant metastatic site to lung and pleura were also demonstrated. However, no association between fatty liver and distant metastasis or metastatic sites in tumour size of <5cm.